Effect of Dates of Sowing and Topping on Seed Production of Jute (Corchorus spp.) - S.R. MORE; S.B. RAJMANE; P.P. SURANA; S.S. MEHETRE; V.S. WANI (Seed Research, 2026)
The study of sowing dates and topping in two varieties of Jute at Rahuri during the year 2000, 2001 and 2002 revealed that there was significantly higher seed yield at 15 June sowing and delay in sowing decreased the seed yield. Variety JRO-524 gave significantly higher seed yield than variety JRC-212. Topping at 45 DAS gave significantly higher seed yield than either topping at 60 DAS, or without topping at normal and dense plant population.